Agouti C57BL/6N embryonic stem cells for mouse genetic resources - Pettitt, Stephen J. (2009)
We report the characterization of a highly germline competent C57BL/6N mouse embryonic stem cell line, JM8. To simplify breeding schemes, the dominant Agouti coat color gene was restored in JM8 cells by targeted repair of the C57BL/6 nonagouti mutation. These cells provide a robust foundation for large-scale mouse knockout programs that aim to provide a public resource of targeted mutations in the C57BL/6 genetic background.